PEASANT AND SCIENTIFIC KNOWLEDGE ON PLANOSOLS AS A SOURCE OF MATERIALS IN THE MAKING OF NON-INDUSTRIAL POTTERY - Raiana Lira Cabral (Revista Brasileira de Ciência do Solo, 2015)
Ethnopedological studies have mainly focused on agricultural land uses and associated practices. Nevertheless, peasant and indigenous populations use soil and land resources for a number of additional purposes, including pottery. In the present study, we describe and analyze folk knowledge related to the use of soils in non-industrial pottery making by peasant potters, in the municipality of Altinho, Pernambuco State, semiarid region at Brazil. Ethnoscientific techniques were used to record local knowledge, with an emphasis on describing the soil materials recognized by the potters, the properties they used to identify those soil materials, and the criteria employed by them to differentiate and relate such materials. The potters recognized three categories of soil materials: “terra” (earth), “barro” (clay) and, “piçarro” (soft rock). The multi-layered arrangement of these materials within the soil profiles was similar to the arrangement of the soil horizon described by formal pedologists. “Barro vermelho” (red clay) was considered by potters as the principal ceramic resource. The potters followed morphological and utilitarian criteria in distinguishing the different soil materials. Soils from all of these sites were sodium-affected Alfisols and correspond to Typic Albaqualf and Typic Natraqualf in the Soil Taxonomy (Soil Survey Staff, 2010).